Unveiling Misogyny: A Critical Comparative Study of the Representation of Women in Avant-garde and Postmodern British Literature - BEKKOUCHE, Fatima Zohra Batoul (My University, 2023)
In the case of literature, grand narratives such as patriarchy, misogyny, and gender roles can influence the way male authors write female characters, while local narratives such as personal experience, cultural background, and empathy can provide opportunities for diverse and nuanced representations. This study investigates the causes of misogynistic and stereotypical depictions of female characters in avant-garde literature. It questions if male authors should be excused for writing sexist texts just because they are intellectuals or because of the time they lived in, and the mindset their society pushed on them. It also aims to see how post-modern female authors' such as Jeannette Winterson reacted to the distortion of women’s image and value. For the accomplishment of this task, two avant-garde novels are closely read, Dr Jekyll and Mr. Hyde by Robert. L Stevenson and The Picture of Dorian Gray by Oscar Wilde, along with Jeannette Winterson’s postmodern novel, The Passion, while employing Jean-Francois Leotard’s theory of meta-narrative as a framework. Drawing on feminist and literary theory, this study contributes to the ongoing discourse on misogyny, feminism, and gender roles.
Keywords: Avant-garde; Female Characters; Feminism; J. F. Leotard; Gender; Sexism; Stereotypes